Influência da duração da oxidação térmica no comportamento à fadiga da liga Ti-6Al-4V - Lima, Gustavo Dória (2019)
The thermal oxidation of titanium alloys is a technique studied to improve the tribological performance, despite its evidences of loss of performance in fatigue. Thermal oxidation treatment of Ti-6Al-4V alloy was performed in air at 600 °C for 2, 5 and 10 h. The fatigue behavior were evaluated and compared with those of the untreated one. The characterization was performed through optical and electronic microscopy, x-ray diffraction, microhardness and roughness measurements. The results of the XRD showed a growth of the rutile peaks when increasing the treatment time from 2 to 10 h. Microhardness and roughness were also elevated by increasing treatment time up to 10 h. There was an increase in mean thickness from 0.12 μm to 1.09 μm, increasing the treatment duration from 2 to 5 h. The results indicated a reduction in the fatigue limit of samples subjected to oxidation. The results indicated a reduction of 35% for oxidized samples for 2 h, 27% for oxidized samples for 5 h and 29% for samples treated for 10 h, in relation to the test with untreated specimens. The detrimental effect caused by the layer formed after oxidation for 2 h was as damaging as that caused by the layer formed after 10 h, even if presented with a higher thickness. The morphology found in the fractured samples indicated embrittlement on the surface of the oxidized samples, contributing to the nucleation of initial cracks in the layer that favored the propagation of fatigue, independent of the layer thickness.